Characteristics of the Preservice Singer/Singing Teacher’s Ethnocultural Competence Components - Vitalii Simonian (Pedagogical Discourse, 2022)
The purpose of the article is to distinguish the structure of the ethnocultural competence and its content based on theoretical analysis of the researched phenomenon in the scholarly works. In order to investigate the issue there were used theoretical methods including but not limited to analysis, synthesis, generalization, and comparison to study the components of the ethnocultural competence in the field of musical art. This enables to analyze the structure of the preservice singer/singing teacher’s ethnocultural competence and to characterize its components. The findings related to the theoretical analysis of the characteristic structure of ethnocultural competence of the preservice music art teachers, preservice music teachers, preservice music and choreography teachers, preservice music teachers in the regional context, preservice music teachers in higher education, preservice music teachers in pedagogical universities are presented. The main differences in the components of the ethnocultural competence of the preservice singer/singing teacher’s ethnocultural competence have been established. The components of the preservice singer/singing teacher’s ethnocultural competence are identified and characterized. Taking into account the different approaches found in various publications related to the topic under investigation, the structure that characterize the preservice singer/singing teacher’s ethnocultural competence has been introduced. It includes four components among which a motivational and value-related component aiming at improving the individual motivation and activity in mastering the necessary level of professional training, a cognitive component which outlines the individual’s awareness of the traditions and cultural values that belong to the ethnic group, features of their lifestyle, worldview and provides not only knowledge of the culture, but also establishes the creative interaction between different ethnic musical cultures, an operational component that covers the formation of ethno-cultural thinking, contributing to the cognitive processes activation due to the mechanism of thinking operations involved, since ethnocultural thinking possesses all functions, and a reflexive component that characterizes the capacity of an individual to self-assess oneself as a representative of an ethnic group, and their attitude to the cultural traditions of other ethnic groups, aiming at self-knowledge and understanding of the spiritual world, actions and states, role and place in work.